Calligraphic Semiotic Interpretation in Jewelry Design: Culture, Identity and Expression - Liang, Kun (Journal of Ecohumanism, 2024)
This article places the application of calligraphy in jewelry design under the perspective of semiotic research. It is a targeted study based on whether calligraphy can be organically integrated with semiotic characteristics for jewelry design. Supplemented by qualitative analysis, based on the relationship between the form and connotation of calligraphy and the signifier and the signified in semiotics, the positive impact of the integration and mutual promotion of calligraphy semiotics and jewelry design was deeply explored. This article first introduces the principles of semiotics, cultural semiotics and the research theory of traditional Chinese cultural symbols, then explains the essential characteristics and significance of jewelry design, and then focuses on the multi-dimensional and diversified connection between calligraphy, jewelry design and semiotics. After discussion and research, we finally reflected on jewelry design and attached relevant suggestions. The perspective chosen in this article is one of the outstanding features of this study. Although calligraphy and symbols originated from different cultural backgrounds in the East and the West, they have common attributes and functions that can be learned from each other. Based on the theoretical intersection of calligraphy and semiotics, the value and application of the combination of calligraphy symbols and jewelry design are discussed, which fully illustrates the close connection between Chinese calligraphy and semiotics and jewelry design. This article attempts to start with Chinese calligraphy and use semiotic research as a guide to construct a more practical "symbol"-"calligraphy"-"culture" jewelry design model. Through theoretical framework analysis, literature review, and empirical research, this article delves into how calligraphic symbols contribute to cultural heritage conservation, personal identity expression, and artistic expression in the context of jewelry design.